Pixel walking along the boreal forest–Arctic tundra ecotone: Large scale ground-truthing of satellite-derived greenness (Normalized Difference Vegetation Index (NDVI)); 2020 ... - Wong, Russell; Berner, Logan; Sullivan, Patrick; Potter, Christophoer; Dial, Roman (NSF Arctic Data Center, 2024)
This dataset includes the sampling of 24,395 Landsat pixels (30 meters (m)) using 639 kilometers (km) of vegetation transects across Alaska's central Brooks Range in 2020. Satellite observations, which are essential for monitoring changes at ecosystem scales, require field data for interpretation. This dataset contains long, continuous vegetation transects collected at spatial scales that closely match the resolution of remotely sensed imagery. Additionally, the dataset contains derived Landsat data that relate ground-based observations to satellite derived maximum growing season Normalized Difference Vegetation Index (NDVI) (peak-greenness). Vegetation transects were collected on smartphones while walking. Along these transects, we classified overstory and understory vegetation data at the scale of ~900 square meters (m2). Field transects were then matched to Landsat pixels where we estimated peak-greenness using phenological modelling. ...